Mechanism of exercise-derived circulating exosomes as a target for sarcopenia management - Wang, Xiangbo; Huang, Hui; Chen, Jie; Zhang, Qing; Yuan, Zhichao; Yin, Mingyue; Peng, Chenggen; Liu, Songlin (Frontiers in Physiology, 2026)
Sarcopenia, an age-related syndrome characterized by the progressive decline of skeletal muscle mass and function, threatens the health of older adults through underlying mechanisms that include dysregulated protein metabolism, autophagy-mitochondrial dysfunction, chronic inflammation, and impaired regenerative capacity of muscle stem cells. Exercise-derived circulating exosomes, which act as key mediators of intercellular communication, show considerable potential in mitigating sarcopenia-related damage. In this review, we summarize the biogenesis of exercise-induced exosomes, encompassing both ESCRT-dependent and independent pathways, secretion regulated by RAB and SNARE proteins, and their release mediated through mechanical, calcium, metabolic, and neuroendocrine signaling during exercise. We further elaborate on the systemic roles of these exosomes in muscle repair, including alleviating lipotoxicity via the FGF21-adiponectin axis, maintaining protein homeostasis through dual regulation by miR-29c, and ameliorating the inflammatory microenvironment via modulation of macrophage polarization. Finally, we discuss the translational promise of exosomes as therapeutic targets and outline future research directions, offering a conceptual framework for understanding exercise-mediated muscle protection and developing novel interventions.